Evaluation of the triangular fibrocartilage: comparison of two-compartment wrist CT arthrography using the distal radioulnar and radiocarpal joints and unicompartment wrist CT arthrography using the radiocarpal joint - Kim, Sujin (Br J Radiol, 2019)
OBJECTIVE: To compare the diagnostic performance of two-compartment wrist CT arthrography of the distal radioulnar and radiocarpal joints and unicompartment wrist CT arthrography of the radiocarpal joint in depiction of the triangular fibrocartilage tear. METHODS: From January 2016 to December 2017, two-compartment CT arthrography of 74 consecutive patients (36 females, 38 males; mean age, 37.2 years) and unicompartment CT arthrography of 51 consecutive patients (18 females, 33 males; mean age, 40.1 years) were obtained. All CT arthrography images were independently and blindly evaluated by two radiologists for the presence of the triangular fibrocartilage tear by grade (partial or full thickness) per its locations: central disc proper, central-peripheral junction, proximal and distal laminae of its ulnar attachment. Fisher’s exact test was used for a statistical analysis, and a p-value less than 0.05 was considered as significant. The arthroscopic findings of 47 patients (34 patients with two-compartment CT arthrography and 13 patients with unicompartment CT arthrography) were evaluated for calculating sensitivity, specificity, and accuracy. RESULTS: All partial and full thickness triangular fibrocartilage tears were identified more commonly by their location except for distal laminae on two-compartment CT arthrography than were unicompartment CT arthrography (p = 0.001–0.022). Two-compartment CT arthrography had high sensitivity (90.9–100%) and low specificity (33.3–76.5%) for detecting central disc proper and proximal lamina tears, comparing with unicompartment CT arthrography. CONCLUSION: Two-compartment wrist CT arthrography is more helpful for detecting triangular fibrocartilage tears than unicompartment wrist CT arthrography. ADVANCES IN KNOWLEDGE: It could be important to evaluate the ulnar foveal insertion of the TFCC in clinical practice, which plays the most important role in DRUJ instability and ulnar-sided wrist pain. Two-compartment wrist CTA of the DRUJ and RCJ could improve diagnostic sensitivity in the TFC tear in terms of its location and torn degree over that of unicompartment wrist CTA of the RCJ. Two-compartment wrist CTA of the DRUJ and RCJ may be recommended as a diagnostic imaging, rather than unicompartment wrist CTA of the RCJ, when peripheral foveal tear of TFC is suspected, especially in young patients.